"Common" Instruction? Logics of Ability and Teacher Decision Making Across Tracks in the Era of Common Standards. (June 2019) - Hodge, Emily M.
This article investigates the interaction between the Common Core State Standards and curricular tracking by examining instructional decision making across tracks in a large metropolitan district. This study draws on institutional logics as a framework to analyze 106 instructional decisions from 24 participants involved in middle school literacy instruction. In lower-track classes, participants often adapted the curriculum and adopted a more teacher-centered approach. About half of the rationales for those decisions reflected a logic of tracking, less than a fifth reflected a logic of differentiation, and almost a third reflected elements of both logics. These findings demonstrate that despite common standards, a tracked school structure continues to serve as a powerful signal about the curriculum and instruction seen as appropriate for different groups of students.